2010
DOI: 10.1186/1471-2288-10-71
|View full text |Cite
|
Sign up to set email alerts
|

The impact of attrition on the representativeness of cohort studies of older people

Abstract: BackgroundThere are well-established risk factors, such as lower education, for attrition of study participants. Consequently, the representativeness of the cohort in a longitudinal study may deteriorate over time. Death is a common form of attrition in cohort studies of older people. The aim of this paper is to examine the effects of death and other forms of attrition on risk factor prevalence in the study cohort and the target population over time.MethodsDifferential associations between a risk factor and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 11 publications
3
70
0
Order By: Relevance
“…The attrition rates vary considerably between the included studies, and most of them did not explain these rates. Death is a common cause of attrition in cohort studies of older people,78 which affects the accuracy of the models. Only some studies in this SR took this into account 39 41 45 47 48 57 58 61 62 64.…”
Section: Discussionmentioning
confidence: 99%
“…The attrition rates vary considerably between the included studies, and most of them did not explain these rates. Death is a common cause of attrition in cohort studies of older people,78 which affects the accuracy of the models. Only some studies in this SR took this into account 39 41 45 47 48 57 58 61 62 64.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, previous studies of lung function decline have not implemented formal statistical methods to account for attrition. Previous studies of other outcomes have handled attrition using different methods [28,29]. For example, under attrition missing-at-random assumptions, longitudinal random effects [30] and traditional inverse-probability-weighted regression [31] approaches have addressed the potential bias resulting from the diminished representativeness of the study population at later visits through specification of the intra-subject correlation structure or the use of weights derived from a model that does not distinguish between sources of attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed mailed surveys in 1996, 1999, 2002, 2005, 2008 and 2011. At baseline, the women were largely representative of women aged 70–75 years in the Australian population, and analyses have shown that attrition has not resulted in bias for studies assessing mortality 15 16. More details can be found at http://www.alswh.org.au.…”
Section: Methodsmentioning
confidence: 99%